Feasibility and acceptability of esophageal‐directed hypnotherapy for functional heartburn. Issue 5 (30th March 2015) - Riehl, M. E.; Pandolfino, J. E.; Palsson, O. S.; Keefer, L.
Summary: Functional heartburn (FH) is a benign but burdensome condition characterized by painful, burning epigastric sensations in the absence of acid reflux or symptom‐reflux correlation. Esophageal hypersensitivity and its psychological counterpart, esophageal hypervigilance (EHv) drive symptom experience. Hypnotherapy (HYP) is an established and preferred intervention for refractory symptoms in functional gastrointestinal disorders (FGIDs) and could be applied to FH. The objective of this study was to determine the feasibility, acceptability, and clinical utility of 7 weekly sessions of esophageal‐directed HYP (EHYP) on heartburn symptoms, quality of life, and EHv. Similar to other work in FGIDs and regardless of hypnotizability, there were consistent and significant changes in heartburn symptoms, visceral anxiety, and quality of life and a trend for improvement in catastrophizing. We would recommend EHYP in FH patients who are either non‐responsive to medications or who would prefer a lifestyle intervention.